Conceptions of marriage readiness and marital quality indicators for future wellbeing among emerging adult students in the university of buea, Cameroon - Lo-oh , Joseph Lah (American Journal of Social Sciences and Humanities, 2023)
While marriage is still strongly held as a major transition event for young people moving through emerging adulthood to full adult status, their conceptions of marriage readiness are diverse, and individually and socio-culturally rooted but also contested. Where their perceptions of marriage readiness are not contested, their beliefs about what it means to be ready for marriage are somewhat paradoxical in most cases. This paper presents descriptive data on youth-held conceptions of marriage readiness, the pathways to marriage and marital quality indicators for future wellbeing among some emerging adults in the University of Buea in Cameroon. A sample of 124 emerging adults, aged 18-30 responded to an adapted Criteria for Marriage Readiness questionnaire whose reliability was 0.848. Data showed that 72.9% of respondents felt that the criteria defined in the study were necessary for marriage readiness; whereas 27.1% did not see the criteria as necessary. Sought whether the criteria defined were important and at what level for future marital quality and wellbeing, 48.7% felt that the criteria defined were very important, 18.6% said the criteria were quite important, 17% maintained that the criteria defined were slightly important while 15.7% felt that the criteria were not at all important. Generally, thinking about marriage and marriage readiness against future marital satisfaction and wellbeing was an important function in the lives of emerging adults. It was concluded that conceptions of marriage readiness among them do not only connote readiness for marriage but further predict future marital satisfaction and wellbeing.